Racial and Ethnic Inequities to Cumulative Environmental and Occupational Impacts in Michigan - Abas Shkembi; Sung Kyun Park; Jon Zelner; Richard Neitzel (GeoHealth, 2025)
Abstract The contribution of occupational exposures to the extent of cumulative environmental impacts, and their implications for environmental justice (EJ), have not been investigated. We (a) characterized communities with cumulatively high occupational and environmental exposures, (b) examined whether marginalized, historically redlined neighborhoods were disproportionately affected by these exposures, and (c) evaluated the implications of failing to consider workplace exposures in EJ screening tools in Michigan. At the census tract‐level, we combined occupational exposure estimates of six common workplace hazards, environmental exposures from EJScreen and the National Transportation Noise Map, demographic information from the American Community Survey, and redlining information from the 1930s Home Owners' Loan Corporation maps to test the first two objectives using supervised and unsupervised statistical methods. The last objective incorporated the occupational indicators into the Michigan‐specific EJ screening tool (MiEJScreen) to test the third objective. Among 2,772 Michigan census tracts, 738 (27%) had cumulatively high occupational and environmental exposures, primarily in urban areas. Tracts with >90% (compared to <10%) of racial and ethnic minority individuals had 2.31 (95% CI: 1.78–3.03) times higher odds of cumulatively high exposures. A simultaneous increase to the 90th percentile (relative to the 50th) in all 13 occupational and environmental exposures was associated with 2.47 (95% CI: 1.20–5.36) times higher odds of a tract having been historically redlined. Not incorporating occupational exposures into the MiEJScreen would overlook 90 census tracts with cumulatively high environmental and occupational impacts, affecting around 255,000 individuals. Ignoring occupational exposures in cumulative environmental impact assessments may overlook important EJ hotspots.